2020
DOI: 10.1002/btm2.10196
|View full text |Cite
|
Sign up to set email alerts
|

IDentif.AI: Rapidly optimizing combination therapy design against severe Acute Respiratory Syndrome Coronavirus 2 (SARS‐Cov‐2) with digital drug development

Abstract: The emergence of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) led to multiple drug repurposing clinical trials that have yielded largely uncertain outcomes. To overcome this challenge, we used IDentif.AI, a platform that pairs experimental validation with artificial intelligence (AI) and digital drug development to rapidly pinpoint unpredictable drug interactions and optimize infectious disease combination therapy design with clinically relevant dosages. IDentif.AI was paired with a 12-drug can… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
43
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

6
2

Authors

Journals

citations
Cited by 29 publications
(44 citation statements)
references
References 48 publications
(98 reference statements)
0
43
0
Order By: Relevance
“…The authors also suggested the utilization of this platform for COVID-19 intervention. Blasiak et al (2021) utilized IDentif.AI to evaluate over 530,000 drug combinations against the SARS-CoV-2 live virus collected from a patient sample. IDentif.AI identified the combination of remdesivir, ritonavir, and lopinavir as a potentially effective treatment against SARS-CoV-2 infection.…”
Section: Resultsmentioning
confidence: 99%
“…The authors also suggested the utilization of this platform for COVID-19 intervention. Blasiak et al (2021) utilized IDentif.AI to evaluate over 530,000 drug combinations against the SARS-CoV-2 live virus collected from a patient sample. IDentif.AI identified the combination of remdesivir, ritonavir, and lopinavir as a potentially effective treatment against SARS-CoV-2 infection.…”
Section: Resultsmentioning
confidence: 99%
“…Kaletra has gone through extensive clinical trials for COVID-19 but shows limited efficacy by itself 31,32 . Recently, using a digital drug development approach combining artificial intelligence and experimental validation to screen drug combinations for potential combination therapy against SARS-CoV-2, it was determined that one of the most effective potential combinations was Remdesivir, Ritonavir and Lopinavir 33 . This synergy of Ritonavir and Lopinavir with Remdesivir may be due to the exonuclease inhibitory activity of these two drugs (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…The first permutation of IDentif.AI used neural networks to reveal that the biological response to therapy can be represented by a smooth surface. Subsequent studies resolved this surface, which can rapidly identify optimal combinations, using a second-order algebraic function, with its coefficients determined through a small number of prospective experiments (Abdulla et al, 2020;Al-Shyoukh et al, 2011;Blasiak et al, 2021;Clemens et al, 2019;Ho, 2020;Ho et al, 2020;Lee et al, 2017;Lim et al, 2020;Mohd Abdul Rashid et al, 2015;Rashid et al, 2018;Silva et al, 2016;Wang et al, 2015;Wong et al, 2008). This correlation has subsequently been verified in prospective, human studies in infectious disease, cancer therapy, transplant medicine, and other indications (Tan BKJ et al, 2021;Blasiak et al, 2020;de Mel et al, 2020;Kee et al, 2019;Pantuck et al, 2018;Shen et al, 2020;Zarrinpar et al, 2016).…”
Section: Introductionmentioning
confidence: 92%
“…RDV and EIDD-1931 were the only drugs that achieved EC50 < Cmax with Cmax /EC50 ratios of 2.92 and 11.46, respectively. RDV, RTV and LPV performance in monotherapy was comparable with that observed in the previous IDentif.AI study based on the same assay (Blasiak et al, 2021).…”
Section: Monotherapies Were Broadly Not Sufficiently Efficacious In the Actionable Dosing Rangementioning
confidence: 99%
See 1 more Smart Citation